Pediose gland in land snails and its evolutionary implications, with emphasis on Megalobulimus - Borda, Victor (2010)
We describe the anatomy of pediose gland in five species of Megalobulimus (Megalobulimidae) and contrast them with those of succineid, orthalicid and helicid gastropods. The presence of a membrane that isolates the pediose gland from the visceral cavity is a synapomorhy of the Stylommatophora clade. A variable range of fixation of the gland to the muscular foot is observed in studied species, from a gland barely held by few fibers (Megalobulimus) to a totally isolated gland (Cantareus), passing through different intermediate grades (Succinea and Bostryx). The pediose gland in Heterovaginina limayana (Systelomatophora) is not attached to the bottom of the visceral cavity. The glandular portion is a voluminous structure that dangles from the capsule roof in Megalobulimus, whereas in other species it is attached to the capsule internal wall. We describe new pediose gland characteristics that reinforce diagnosis of the genus Megalobulimus and provide more phylogenetic information.